Guilty pleasures - Hamilton, Laurell K. (Hamilton, Laurell K. Anita Blake, vampire hunter novel, 2023)
Vampire hunter Anita Blake must shift her attention from catching vampires to helping them when she is hired to stop a serial killer from murdering any more vampires.